Mental and Physical Well-Being of Partners of People Living with Chronic Pain: A Narrative Review - Newton-John, Toby RO; Cave, Shari; Bean, Debbie (MDPI AG, 2025)
This narrative review aims to explore the mental and physical well-being of partners of individuals living with chronic pain. Chronic pain not only affects those who suffer from it, but also significantly impacts the lives of their partners; however, the impacts on partners are not well recognised, despite extensive evidence indicating that their quality of life can be equally affected. This review synthesises current literature to identify the psychological and physical challenges faced by these partners, including increased stress, anxiety, depression, and the potential for developing chronic health conditions themselves. A search of Medline for “chronic pain” and “partner/spouse” from January 1990 to the present was performed, and relevant articles were selected for review. The main findings were that while partners often experience a range of negative physical and psychosocial impacts on their quality of life, dyadic coping strategies can mitigate these effects. This review underscores the importance of future research to develop targeted interventions that address the unique needs of this population, promoting better health outcomes and fostering resilience in the face of chronic pain.
Keywords: 32 Biomedical and Clinical Sciences; 4203 Health Services and Systems; 4205 Nursing; 3202 Clinical Sciences; 42 Health Sciences; Depression; Brain Disorders; Pain Research; Mental Health; Chronic Pain; Mental Illness; Behavioral and Social Science; Neurosciences; 7.1 Individual care needs; 6.6 Psychological and behavioural; 2.3 Psychological, social and economic factors; Generic health relevance; Mental health; 3 Good Health and Well Being; Toxicology